Issues of Affiliation in the Engineering Industry - Cheng, Qian (International Journal of Social Sciences and Public Administration, 2024)
Due to the implementation of the enterprise qualification management system in the engineering industry in China, there are certain requirements for the construction companies that undertake projects. However, in practice, many projects do not have high requirements for construction capabilities, and even those who don’t have corresponding qualifications can complete the construction of the project and meet the quality requirements. This has led to a large number of construction companies that do not meet the qualification requirements and even construction teams composed of natural persons borrowing the names of other enterprises to undertake projects. Although it is expressly prohibited in legislation, it can’t be stopped completely in practice. This paper will analyze the causes of this phenomenon and propose improvement suggestions, in order to promote the long-term healthy development of the engineering industry.